Dynamic modelling of a compressed heat energy storage (CHEST) system integrated with a cascaded phase change materials thermal energy storage - Tafone, Alessio (2023)
Carnot batteries represent an emerging thermo-mechanical energy storage technology based on the conversion of surplus electricity into medium–low temperature heat, and subsequent conversion of the heat into electricity. A promising Carnot battery's configuration is the Compressed Heat Energy Storage (CHEST) that combines a high-temperature heat pump (charge phase), an Organic Rankine Cycle (discharge phase) and a thermal energy storage (TES) system. As of now, all the literature studies on CHEST were designed to store the thermal energy into a cascaded TES combining a pressurized water storage for the sensible section and latent heat material for the evaporation and condensation sections. The objective of the present work is to numerically investigate a novel configuration of the TES system utilizing a cascade of multiple phase change materials (PCMs) in place of the cascade of sensible heat and phase change materials presented in literature, aiming to enhance both the energy density and the round trip efficiency of the system. The comparative technical analysis has been carried out by developing for the first time a dynamic numerical model of the CHEST system. Indeed, while the current literature studies on CHEST are only focused on preliminary analyses to define the general thermodynamic potential and to identify the limits of the overall system, this paper overcomes this gap and presents a detailed dynamic analysis of the CHEST with focus on TES modelling. Notably, the authors developed a plant model in MATLAB that blends together algebraic and differential sub-models detailing the transient behaviour of the CHEST system. The results are of interest for academia and industry and contribute significantly to the development of a more efficient CHEST system. Indeed, by enhancing the thermal buffer effect typical of PCM media, the cascaded TES augments both the COP of the high-temperature heat pump (4.13 vs 3.79) and the electric efficiency of the ORC (11.69 % vs 11.31 %). As a result, the novel CHEST system based on cascaded PCMs is capable to achieve a round trip efficiency of 47.6 % and an energy density of 6.9 kWhe/m3, simultaneously increasing the respective values of the state-of-the-art solution by 13 % and 100 %, respectively.